Suitability of Antitrust Immunity Law in the Assignment of the Covid-19 Vaccine to PT Bio Farma (Persero) - Shela Intan Sari; Siti Anisah (International Journal of Law, Environment, and Natural Resources, 2022)
In early 2020, the global shock of the Covid-19 outbreak led to the rapid development of vaccines in several countries. In Indonesia, PT Bio Farma was designated by the government to procure Covid-19 vaccines, as outlined in Presidential Regulation Number 99 of 2020. This study examines the legality of PT Bio Farma's direct appointment in vaccine procurement under business competition law and its compliance with antitrust immunity. Through normative legal research, it is found that while some regulations are adhered to, others are violated by the government, indicating that PT Bio Farma's direct appointment does not align with principles of fairness and economic democracy in business competition law. Moreover, Presidential Decree No. 99 of 2020 provides antitrust immunity, subject to fulfilling specific criteria, in line with certain articles of the Antitrust Law, as an exception to the prohibition of monopolistic practices.